Correlation of Cartridge Based Nucleic Acid Amplification Test Grading Based on Cycle Threshold Value with Clinicoradiological Profile and Time to Culture Positivity in Pulmonary Tuberculosis Patients: A Cross-sectional Study - Mohammed Javed Qureshi; Bhanu Pratap Choudhary; Chand Bhandari; Harsh Maheshwari; Manoj Saini; Dheeraj Merotha (Journal of Clinical and Diagnostic Research)
Introduction: Tuberculosis (TB) remains a global health challenge, with India bearing the highest burden, including Multidrug-Resistant (MDR) TB. Early diagnosis is critical in controlling transmission, often achieved using GeneXpert Mycobacterium tuberculosis/Rifampicin (MTB/RIF), which detects TB bacilli, RIF resistance and provides Cycle Threshold (CT) values reflecting bacillary load. Correlating CT values with clinical, radiological and microbiological parameters can enhance the evaluation of disease severity and guide management. Aim: To evaluate the correlation of Cartridge Based Nucleic Acid Amplification Test (CBNAAT) CT values with clinical, radiological and microbiological parameters to assess bacillary load and disease severity in pulmonary TB. Materials and Methods: This cross-sectional study was conducted at Institute of Respiratory Diseases, Sawai Man Singh Medical College, Jaipur, Rajasthan, India from April 2023 to April 2024. Patients diagnosed with pulmonary TB based on CBNAAT were enrolled. The study period spanned 12 months. The study included 110 participants (calculated for 95% confidence, 80% power and 7.5% error, based on 62% smear-positive prevalence and 90.5% GeneXpert sensitivity). Eligible participants were adults (≥18 years) providing consent, including all sputum smear-positive cases and smear-negative suspects. Patients with extrapulmonary TB, undetectable sputum CBNAAT-MTB, and pregnant women were excluded. Data collected included name age, sex, symptoms and signs (cough, expectoration, fever, breathlessness, weight loss, chest pain, haemoptysis, clubbing, icterus, pallor, cyanosis, lymph node, oedema, chest examination), vitals (blood pressure, oxygen saturation, heart rate, temperature, respiratory rate, Body Mass Index (BMI), mid upper arm circumference) Bandim scores, co-morbidities and demography, Chest X-ray (CXR) grading, sputum fluorescent microscopy grading and time to positivity in liquid culture. Correlation analyses were performed using Spearman’s rho and Pearson’s tests. IBM Statistical Package for the Social Sciences (SPSS) version 29.0 was used for statistical analysis, and a p-value <0.05 was considered significant. Results: The study included 110 patients, with the largest group (41) aged 21-40 years, followed by 30 patients in the 41-60 years age range. The mean age of the participants was 44.93±18.07 years. It demonstrated significant correlations between CBNAAT CT values and various diagnostic parameters. CBNAAT CT values were inversely correlated with Bandim scores (Spearman’s rho=-0.82, p-value <0.001), chest X-ray grading (Pearson’s r-value=-0.429, p-value=<0.001), and sputum fluorescent microscopy grading (Spearman’s rho=-0.63, p-value=<0.005), indicating lower CT values were associated with higher bacillary loads. Conversely, a positive correlation was observed between CBNAAT CT values and liquid culture time to positivity. Bivariate analysis showed that high bacillary loads were significantly associated with higher Bandim scores, advanced chest X-ray grading and elevated sputum microscopy grading (p-value <0.05). Conversely, low bacillary loads were characterised by higher CBNAAT CT values, milder radiological findings and reduced sputum microscopy grading. These findings underscore the utility of these variables in distinguishing between low and high bacillary load cases. Conclusion: CBNAAT CT values are strongly correlated with clinical, radiological and microbiological parameters in pulmonary TB. Lower CT values are indicative of higher bacillary loads, while higher CT values suggest lower bacillary loads. These findings highlight the potential of CBNAAT CT values as a surrogate marker for bacillary burden in pulmonary TB.